2016
DOI: 10.1016/j.jenvman.2016.07.100
|View full text |Cite
|
Sign up to set email alerts
|

Sludge reduction by uncoupling metabolism: SBR tests with para-nitrophenol and a commercial uncoupler

Abstract: Nowadays cost reduction is a very important issue in wastewater treatment plants. One way, is to minimize the sludge production. Microorganisms break down the organic matter into inorganic compounds through catabolism. Uncoupling metabolism is a method which promote catabolism reactions instead of anabolism ones, where adenosine triphosphate synthesis is inhibited. In this work, the influence of the addition of para-nitrophenol and a commercial reagent to a sequencing batch reactor (SBR) on sludge production a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The high stress caused by the quick conductivity increase and the high increase of the ammonium nitrogen concentration were responsible for the cell lysis. Furthermore, it was detected a direct relation between DNA and protein concentrations, what corroborates that measured proteins could come from the released cellular material from the bacteria, as previously published Zuriaga et al [42].…”
Section: Biomass Characteristicssupporting
confidence: 88%
“…The high stress caused by the quick conductivity increase and the high increase of the ammonium nitrogen concentration were responsible for the cell lysis. Furthermore, it was detected a direct relation between DNA and protein concentrations, what corroborates that measured proteins could come from the released cellular material from the bacteria, as previously published Zuriaga et al [42].…”
Section: Biomass Characteristicssupporting
confidence: 88%
“…The analysis of DNA was studied to observe whether cell lyses occurred. 43 In this case, for SBR, DNA concentrations did not vary significantly with the operation time. However, for OMBR, DNA concentration decreased with operation time, which indicates that biomass was adapted progressively to the operating conditions of the OMBR.…”
Section: Comparison Of Ombr and Sbrmentioning
confidence: 66%
“…The analysis of DNA was studied to observe whether cell lyses occurred . In this case, for SBR, DNA concentrations did not vary significantly with the operation time.…”
Section: Resultsmentioning
confidence: 84%
“…Prior studies have generally focused on the effects of spiked addition of uncoupling agents to sludge [13], and no studies have examined the extended addition of uncoupling agents. Previous studies by the present authors on spiked addition of 3,5-DCP to similar fed-batch reactors also showed that the capacity of 3,5,-DCP to reduce the quantity of sludge produced was lost in approximately 3 weeks [12].…”
Section: Resultsmentioning
confidence: 99%